Emerging technologies for business professionals a nontechnical guide to the governance and management of disruptive technologies - Vincent, Nishani Edirisinghe; Igou, Amy (Wiley, 2024)
"There is an emerging market need for nontechnical technology information for both students and the C suite. In academia the business college accreditation body AACSB has emphasized the importance of information systems education in the business curricula. For accounting professionals, the AICPA has released a change to the CPA exam (effective 2024) where the CPA evolution model curriculum focuses on emerging technologies and their implications for business. This book will cover Artificial Intelligence (AI), analytics, robotics process automation (RPA), computing (edge computing, cloud computing, quantum computing), blockchain, ancillary technologies (virtual reality/augmented reality, internet of things, 3-D printing, 5G data networks), cybersecurity, and ethics in digital computing."--
Includes index
Keywords: Business enterprises / Technological innovations; Artificial intelligence; Blockchains (Databases); Computer security